2013
DOI: 10.1590/1982-43272354201305
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbio Específico de Linguagem: Caracterização Neuropsicológica

Abstract: This study's objective was to characterize the neuropsychological functioning of children with Specifi c Language Impairment (SLI), in the areas of visual and verbal memory, attention/executive functions, and visual-perceptual functions. The sample consisted of 28 children with SLI and 28 children without SLI. Both groups were comparable in terms of age, gender, school grade and socioeconomic level. The assessment instruments used are part of Coimbra's Neuropsychological Assessment Battery and data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
0
0
4
Order By: Relevance
“…Furthermore, the same study reported below mean scores in other EF such as cognitive flexibility (50%), attention (77.3%), and planning (100%) [13]. As explained before, SLI might have a direct relationship with executive dysfunction since language is important for cognitive regulation and internalized speech; certainly, some studies report significant deficits in phonological working memory, in 69%-86% of cases; short-term auditory memory, in 63% of cases; and visual/verbal memory, in 43%-91% of cases [14,[16][17][18]20,26]. Finally, a couple of studies reported deficits in processing speed and inhibition in 69%-77% of SLI children aged 6-11 years old [18,23].…”
Section: Figure 1: Prisma Flowchartmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the same study reported below mean scores in other EF such as cognitive flexibility (50%), attention (77.3%), and planning (100%) [13]. As explained before, SLI might have a direct relationship with executive dysfunction since language is important for cognitive regulation and internalized speech; certainly, some studies report significant deficits in phonological working memory, in 69%-86% of cases; short-term auditory memory, in 63% of cases; and visual/verbal memory, in 43%-91% of cases [14,[16][17][18]20,26]. Finally, a couple of studies reported deficits in processing speed and inhibition in 69%-77% of SLI children aged 6-11 years old [18,23].…”
Section: Figure 1: Prisma Flowchartmentioning
confidence: 98%
“…Pijnacker (2016) [15] Cross-Sectional Moderate Lidstone (2012) [16] Cross-Sectional Low Coelho (2013) [17] Cross-Sectional Low Lukács (2015) [18] Cross-Sectional Low Willinger (2017) [19] Cross-Sectional Low…”
Section: Figure 1: Prisma Flowchartmentioning
confidence: 99%
See 1 more Smart Citation
“…No que diz respeito às finalidades às quais destinavam-se às avaliações das FE empreendidas, percebeu--se que algumas pesquisas objetivaram com o uso dos instrumentos comparar grupos clínicos, especialmente comparações entre indivíduos que apresentam algum transtorno e/ou doença e outros sem esses quadros, a exemplo do transtorno do pânico (Bolshaw, Greca, Nardi, Júnior, Fonseca, & Fernandez, 2011), traumatismo craniano e acidente cerebrovascular (Morrison et al, 2013 (Coelho, Albuquerque, & Simões, 2013;Duchesne et al, 2010;Hovik et al, 2015;Lopes, 2010;Martino, Strejilevich, & Manes, 2012;Nunes et al, 2014;Pedron, Ferrão, Gurgel, & Reppold, 2015). Corroborando com os resultados apresentados, Bolshaw et al (2011) afirmam que se nota um recente e significativo aumento no número de publicações em busca de um perfil neuropsicológico de quadros psiquiátricos, tendo sido realizados estudos com os mais diversos transtornos mentais e deficiências.…”
Section: Executive Function Performance Test (Efpt)unclassified
“…Alterações de linguagem e de fala podem ser encontradas em crianças com FLP. Investigações apontam que essas crianças tem maior atraso na aquisição das primeiras palavras assim como na produção de sentenças curtas, na recuperação de palavras, na compreensão e produção de linguagem quando comparadas a crianças com desenvolvimento típico (PEGORARO-KROOK et al, 2004;GRUNWELL & SELL, 2005;MILDINHALL, 2012;SCHERER, OKAVKNOVA & MCBEE, 2013;COELHO et al, 2013).…”
Section: Fissuras Labiopalatinasunclassified